Correlation of Spiritual Well-being Psychological Capital among University Students-Iran - Pourmirza Kalhori, Reza; Mohammadzadeh, Hakimeh; Foroughinia, Azadeh; Kianipour, Neda (International Journal of Engineering and Technology, 2018)
Psychological capital is one of the new concepts raised in positivism in psychology, which can play a major role in increasing oneâ€™s ability in different aspects of life, especially in spiritual well-being. Therefore, the present study aimed to investigate the relationship between the components of spiritual well-being and psychological capital of students at Kermanshah University of Medical Sciences, Iran in 2017. In this descriptive-correlational study, the statistical population consisted of 400 students at Kermanshah University of Medical Sciences, who were selected through cluster sampling. To collect the required data, a demographic questionnaire, the spiritual well-beingÂ scale (SWB) by PaloutzianÂ & Ellison and the Â Psychological Capital QuestionnaireÂ (PCQ) by Luthans were used. In addition, the data were analyzed using the SPSS Statistics Software Version 23.0. The results of the present study revealed that the mean scores of students' spiritual well-being and psychological capital measured 3.60 Â± 0.49 and 3.55 Â± 0.44, respectively. Further, the results of Pearson correlation coefficient indicated that the students' spiritual well-being and psychological capital positively and significantly correlated (r=0.42). According to the findings of the present study, the studentsâ€™ spiritual well-being affects their psychological capital. So, it can be concluded that religious orientation and spirituality can promote the psychological capital of individuals, and this approach can be used to provide services relating to mental well-being.Â